Variation in the quality of opioid use disorder treatment in the Medicaid population in 2019 - Ryan M. Andrews; Vishwali Mhasawade; Selena Maity; Anton Hung; Richard Liu; Rachael K. Ross; Hillary Samples; Kara E. Rudolph (PLoS ONE, 2026)
Background This study aimed to describe state- and urbanicity-stratified differences in three opioid use disorder (OUD) treatment metrics among Medicaid beneficiaries in 25 states that implemented Medicaid expansion under the Affordable Care Act by the end of 2014. Methods Using data from 2019, we identified Medicaid beneficiaries with OUD based on ICD-10 diagnosis codes. We then calculated the percentage of beneficiaries who met criteria for three metrics measuring OUD treatment quality, both overall and stratified by state and urbanicity type. The OUD treatment quality metrics considered were: (1) initiation of medication for opioid use disorder (MOUD) treatment, (2) engagement with OUD services, and (3) retention on MOUD treatment. Results Across states, we found that a median of 26.2% of beneficiaries initiated MOUD within 14 days of their OUD diagnosis date in the claims data. A median of 15.8% of beneficiaries engaged with OUD treatment services by initiating MOUD treatment within 14 days of their OUD diagnosis and receiving at least 2 distinct OUD-related services within 30 days of their MOUD initiation date. Among initiators, a median of 30.8% were retained on MOUD treatment for a minimum of 180 days. However, there was considerable heterogeneity in these three metrics across states; New Hampshire and West Virginia were found to have the highest overall performance out of the states considered. With respect to urbanicity, we found that rural and suburban areas had higher percentages of beneficiaries who met our three treatment quality metrics compared to urban areas. Conclusions We found notable geographic differences in opioid use disorder treatment quality in the U.S. Medicaid population.